the Nicholas Monsarrat - Pirates, Nylon (Simon and Schuster, London, 1960)
Nicholas Monsarrat's war, in those dark years of 1939-1945, was a ferocious, unforgiving, terrible war: the Battle of the Atlantic. An RNVR officer, he served on His Majesty's corvettes, tough little ships charged with the impossible task of seeing vital convoys safely through the packs of marauding U-boats. Between watches he kept a record of life on board, the good times and the bad, true tales of heroism, fear and all too often death. This was the war at sea as it really was. The three books were sensationally published even while the war raged about him, and make a fascinating prelude to the post-war The Cruel Sea.
Keywords: Adventure -- Action